Uniaxially crumpled graphene as a platform for guided myotube formation - Kim, Junghoon; Leem, Juyoung; Kim, Hong Nam; Kang, Pilgyu; Choi, Jonghyun; Haque, Md Farhadul; Kang, Daeshik; Nam, Sung Woo (Microsystems and Nanoengineering, 2019)
Graphene, owing to its inherent chemical inertness, biocompatibility, and mechanical flexibility, has great potential in guiding cell behaviors such as adhesion and differentiation. However, due to the two-dimensional (2D) nature of graphene, the microfabrication of graphene into micro/nanoscale patterns has been widely adopted for guiding cellular assembly. In this study, we report crumpled graphene, i.e., monolithically defined graphene with a nanoscale wavy surface texture, as a tissue engineering platform that can efficiently promote aligned C2C12 mouse myoblast cell differentiation. We imparted out-of-plane, nanoscale crumpled morphologies to flat graphene via compressive strain-induced deformation. When C2C12 mouse myoblast cells were seeded on the uniaxially crumpled graphene, not only were the alignment and elongation promoted at a single-cell level but also the differentiation and maturation of myotubes were enhanced compared to that on flat graphene. These results demonstrate the utility of the crumpled graphene platform for tissue engineering and regenerative medicine for skeletal muscle tissues.
Keywords: Cellular assemblies; Chemical inertness; Compressive strain; Crumpled graphene; Mechanical flexibility; Single-cell level; Skeletal muscle; Two Dimensional (2 D)